A novel personal cooling system (PCS) incorporated with phase change materials (PCMs) and ventilation fans: An investigation on its cooling efficiency. (August 2015) - Lu, Yehu; Wei, Fanru; Lai, Dandan; Shi, Wen; Wang, Faming; Gao, Chuansi; Song, Guowen
Abstract: Personal cooling systems (PCS) have been developed to mitigate the impact of severe heat stress for humans working in hot environments. It is still a great challenge to develop PCSs that are portable, inexpensive, and effective. We studied the performance of a new hybrid PCS incorporating both ventilation fans and phase change materials (PCMs). The cooling efficiency of the newly developed PCS was investigated on a sweating manikin in two hot conditions: hot humid (HH, 34 °C, 75% RH) and hot dry (HD, 34 °C, 28% RH). Four test scenarios were selected: fans off with no PCMs (i.e., Fan-off, the CONTROL), fans on with no PCMs (i.e., Fan-on), fans off with fully solidified PCMs (i.e., PCM+Fan-off), and fans on with fully solidified PCMs (i.e., PCM+Fan-on). It was found that the addition of PCMs provided a 54∼78 min cooling in HH condition. In contrast, the PCMs only offered a 19–39 min cooling in HD condition. In both conditions, the ventilation fans greatly enhanced the evaporative heat loss compared with Fan-off. The hybrid PCS (i.e., PCM+Fan-on) provided a continuous cooling effect during the three-hour test and the average cooling rate for the whole body was around 111 and 315 W in HH and HD conditions, respectively. Overall, the new hybrid PCS may be an effective means of ameliorating symptoms of heat stress in both hot-humid and hot-dry environments. Highlights: A portable hybrid PCS incorporated with PCMs and ventilation fans was developed. The cooling efficiency of the PCS was investigated in both hot dry (HD) and hot humid (HH) environments. PCMs provide effective conductive cooling during the initial working period when workers are in the sweat development stage. Compared with PCMs cooling or air ventilation cooling, the hybrid PCS exhibits a significant cooling effect in both hot environments.